Wpływ zmiany liczby godzin zajęć na wyniki egzaminu z matematyki na kierunkach ekonomicznych - Łyko, Janusz; Misztal, Andrzej (The impact of changes in the number of hours of classes on exam results in mathematics at the economic faculties, 2010)
For several years a tendency to reduce the total number of hours of classes in mathematics at several universities of economics could have been observed. At the same time learning curricula have not been a subject to any substantial change, resulting in the need for self-mastery by students of a growing part of the material. An additional difficulty is the more and more stripped-down curriculum for secondary schools. The article attempts to assess the impact of reducing the number of hours on the exams results in mathematics in the fields of finance and accounting, and management. We analyzed data from the academ-ic years 1997/1998-2007/2008 for the Faculties of NE (economic sciences) and ZI (man-agement and information technology) of the Wrocław University of Economics, and the School of Banking in Wrocław
Didactics of Mathematics, 2010, Nr 7 (11), s. 81-92
Keywords: standards of teaching; teaching mathematics; the grading system